ChemInform Abstract: An Intramolecular, Pd‐Mediated α‐Arylation Route to 4‐Aryl‐2‐naphthols. Issue 47 (November 2015) - Aiken, Stuart; Armitage, Ben; Gabbutt, Christopher D.; Heron, B. Mark
Abstract: The short route to the title compounds (V) involves Meyer—Schuster rearrangement of butynol (III) followed by intramolecular α‐arylation.